Hydraulic fracturing and shale gas extraction - Klein, Michael (Kansas State University, 2012)
In the past decade the technique of horizontal drilling and hydraulic fracturing has been improved so much that it has become a cost effective method to extract natural gas from shale formations deep below the earth’s surface. Natural gas extraction has boomed in the past few years in the United States, enough that it has driven prices to an all time low. The amount of natural gas reserves in the U.S. has led to claims that it can lead the country to energy independence. It has also been touted as a cleaner fuel for electricity generation and to power vehicles. This report explains hydraulic fracturing and horizontal drilling particularly with regards to utilizing the techniques for natural gas extraction from shale gas. It also discusses the environmental impact due to the drilling and gas extraction. It demonstrates that although the natural gas beneath the U.S. is a valuable resource, the impacts to the planet and mankind are not to be taken lightly. There is the potential for the effects to be long term and detrimental if measures are not taken now to control them. In addition although on the surface natural gas seems to be a greener fuel, particularly in comparison to gasoline, it is also considered worse for the environment.
Keywords: Hydraulic fracturing; Shale gas; Natural gas; Horizontal drilling; Methane; Chemical Engineering (0542); Environmental Engineering (0775); Natural Resource Management (0528)